Researcher Profiles : Faculty of Chemical Engineering - Wan Kamis, Wan Zuraida; Osman, Mohamed Syazwan; Ismail, Nor Fariza; Senusi, Faraziehan (Faculty of Chemical Engineering UiTM Cawangan Pulau Pinang Kampus Permatang Pauh, 2022)
The Faculty of Chemical Engineering at UiTMCPP is fully equipped with research facilities including technologically advanced equipment that caters for the Master of Science and Doctor of Philosophy degree program via a full research mode. The faculty’s academic staffs have expertise in various research areas in the field of chemical engineering and environmental engineering. The niche area are: Nanotechnology/Nanomaterials, Environmental Technology, Separation Technology, Green Material/Technology, Wastewater Treatment Technology, Catalysis and Reaction Engineering, Renewable Energy, Biomass conversion, Biofuels, Green Energy